Inhibitory processes in language switching: Evidence from switching language-defined response sets - Philipp, Andrea M.; Gade, Miriam; Koch, Iring (European journal of cognitive psychology, 2007)
We used language-defined response sets (digit names from 1 to 9 in different languages) to explore inhibitory processes in language switching. Subjects were required to switch between two (Experiment 1) or among three (Experiment 2) languages. In Experiment 1, we obtained a shift cost when subjects switched between their first and second language, between their first and third language, or between their second and third language. For each language pairing, the shift cost was larger for the relatively dominant language than for the nondominant language (i.e., asymmetric shift cost). In Experiment 2, we assessed inhibition of response sets as reflected in n-2 repetition cost (i.e., the difference between ABA and CBA language sequences). We discuss both effects with respect to inhibitory processes in language switching. The results suggest different functional characteristics of the processes underlying asymmetric shift cost and n-2 repetition cost.